Marxist Reading of Class Inequality in Parable of the Sower - Munte, Nadine; Geni Kurniati (Morphosis: Journal of Literature, 2025)
This study investigates the representation of social class inequality in Octavia E. Butler’s Parable of the Sower, with particular focus on the protagonist, Lauren. Employing Karl Marx’s theory of class struggle, the analysis explores the socio-economic divide between the bourgeoisie and the proletariat, as reflected in the novel’s dystopian society. Through a qualitative literary approach, the research highlights how systemic inequality is embedded in the social and economic structures depicted in the narrative. Lauren’s experiences exemplify the struggles of the working class, illustrating how poverty, exclusion, and exploitation manifest in everyday life. Her resilience and leadership in the face of social collapse serve as a critique of capitalist oppression and as a model of collective resistance. By examining key narrative elements—particularly characterization and plot—the study demonstrates how the protagonist navigates structural barriers and imagines alternative, more equitable futures. Ultimately, this research contributes to broader discussions on class and ideology in literature, emphasizing the enduring relevance of Butler’s work in addressing contemporary socio-political issues such as inequality, marginalization, and survival. The findings underscore literature’s potential to reflect and challenge social injustices through critical engagement with class structures and resistance narratives.